Rec. ad op.: Kuzembayuly A., Abil’ E., Alibek T. The Siberian ulus and Kazakhs: Problems of ethnic continuity and historical memory - Maslyuzhenko D.N. (Золотоордынское обозрение)
Results and scientific novelty. The reviewed book consists of four chapters. The first one is devoted to the history of research of the Shaybanids and the Taibugid statehoods in the south of Western Siberia, as well as to the theoretical and methodological approaches to the issues of ethnic history reconstruction in the Russian and Kazakh historical fields. The second chapter deals with “Historical memory as the source of the history of the Siberian ulus”. It presents memory artefacts of the so-called Siberian ulus in the Kazakh epos poetry and in historical legends on “The materials on Kyrgyz land use”. The sources presented here are virtually unknown to Russian researchers and they open new opportunities for the study of some issues of the late medieval Siberian statehood history. The third chapter raises issues of the prehistory of the Siberian ulus, with special attention given to the ulus of Taibugi, the study of whose descendants has recently taken the lead in Kazakh medieval studies. The fourth chapter is devoted to the history of the Siberian ulus, divided into separate stages (13th–14th centuries, the period of the collapse of the Golden Horde, the Siberian Khanate). The reviewed monograph is an important stage in the formation of modern Kazakh historiography on the issues of further study of the late medieval history of Western Siberia. It reveals some new sources, unknown or little known in earlier Russian historical science; there are interesting and original ideas on ethnic relations of the Siberian and Kazakh population and the origin of the Siberian princely dynasty of the Taibugids, which need further reflection. However, ignoring many achievements of the latest Russian historiography and its selective quoting, refusal to build an accurate chronology, skipping entire decades in the generalising conclusions, and the choice of the term “Siberian ulus”, which has not revealed its full potential, raise the question as to what extent the authors were really able to create a quality study on the role of the Shibanid statehood in the history of the formation of the Kazakh people.